INVESTIGATING THE EFFECT OF ATTRACTIVENESS, EXPERIENCE AND CUSTOMER TRUST ON PURCHASE INTENTION WITH THE MEDIATION OF BRAND EQUITY OF IRANIAN CARS IN IRAQ - Huda Fadhil Gatea (Galaxy International Interdisciplinary Research Journal, 2024)
Over time, the expectations of customers have exceeded the ability of companies to create innovative experiences, and this delay and inability to respond to customers’ needs means the failure of companies to quickly adapt to environmental changes. On the other hand, customers also compare their satisfaction with every purchase and relationship with companies with their level of satisfaction with interactions with top companies. In the meantime, the top companies in each field are more active than ever and are looking for ways to differentiate and overtake their competitors. Therefore, the purpose of this research is to investigate the effect of attractiveness, experience and customer trust on purchase intention with the mediation of brand equity of Iranian cars in Iraq. The research method is practical in terms of the purpose and descriptive and survey in terms of the method. The statistical population includes all the buyers of Iranian cars in Iraq, and it is not possible to obtain an exact volume of them, therefore, the statistical population of customers is of the type of unknown statistical population, and in order to determine the sample size, Cochran’s formula was used, which suggested the number of 384 people. The data collection tool for measuring the variables was Klaus Questionnaire (2020). In the inferential statistics method, using spss software, in each of the hypotheses, the normality of the data was first ensured. Then, the relationship between the variables was analyzed with structural equation method and PLS Smart software, the findings showed that attractiveness, experience, and customer trust have a positive and significant effect on purchase intention through the mediaton of brand equity of Iranian cars in Iraq.